PENGEMBANGAN WISATA DANAU SIAIS SEBAGAI DAYA TARIK WISATA - Mayono Suko Marbinoto; Emrizal Emrizal; Victor Lumban Raja (JURNAL PROINTEGRITA, 2021)
This research was conducted in the tourist attraction of Danau Siais, Angkola Sangkunur District, South Tapanuli Regency. The study aims at finding the development of Lake Siais tourism as a tourist attraction. The development of tourist attractions is an important concept in the world of tourism, by involving tourists and tourism object managers. This research is a descriptive quantitative research. In taking the sample, the accidental sampling formula is used, while for the analysis technique used is the SWOT analysis and Ansoff Matrix Analysis. In this research, there are two problem formulations that are trying to express in this research, namely: 1. What is the potential for the development of Lake Siais as a tourist attraction? 2. What is the strategy for developing Lake Siais as a tourist attraction? The research results have not been optimally realized, this is due to inadequate management, it is necessary to collaborate with investors and the Tourism Office.